False-positive detection of Group B Streptococcus (GBS) in chromogenic media (Strep B Carrot Broth) due to presence of Enterococcus faecalis in High Vaginal swabs. Issue 8 (16th August 2022) - Singh, Abhishek; Husein, Atahar; Singh, Salomi; Ghattargi, Vikas; Dhotre, Dhiraj; Shouche, Yogesh S.; Colaco, Stacy; Abhyankar, Vivek; Patekar, Suyash; Chhabria, Karisma; Kumar, Sushil; Urhekar, A. D.; et al.
Abstract : Introduction. Vaginal colonization of Group B Streptococcus (GBS) is associated with preterm births and neonatal sepsis. Thus routine screening of GBS in prenatal care is recommended. Hypothesis. Chromogenic media (carrot broth) aids in specific and rapid detection of GBS. Aim. To investigate the efficiency of Strep B Carrot Broth for detection of GBS in high vaginal swabs from pregnant women. Methods. In this study 201 vaginal swab samples were collected from pregnant women. Swabs were inoculated in chromogenic media (Strep B Carrot Broth). The positive and negative cultures were inoculated on blood agar and crome agar plates. The colonies were subjected to 16S rRNA sequencing and gene-specific PCR for confirmation. The Christie Atkins Munch Peterson (CAMP) and bile esculin agar (BEA) tests were used for biochemical confirmation. PCR was performed on genomic DNA isolated from uncultured vaginal swabs. Results. It was found that 20/201 (9.9 %) vaginal swab samples were positive in the Strep B Carrot Broth and 17/20 (85 %) and 19/20 (95 %) of these samples yielded colonies on blood agar and crome agar, respectively. Of the 181 carrot broth-negative samples, 1 (0.5 %) and 38 (20.9 %) yielded colonies on blood agar and crome agar plates, respectively. However, 16 s rRNA sequencing revealed that none of the 20 carrot broth-positive cultures were GBS and had sequence similarities to Enterococcus faecalis . This was also confirmed by using gene-specific PCR and BEA positivity. Furthermore, E. faecalis was detected by PCR in DNA isolated from 57 uncultured vaginal swabs samples, GBS could only be detected by PCR in four samples. Conclusion. Carrot broth-based culture can lead to false-positive detection due to the presence of E. faecalis . Thus GBS-positive results in carrot broth must be confirmed by the other molecular and biochemical tests before making a final diagnosis.